Adnan Al-Sayegh's Anti-War Poetry: A Cry Against Inhumanity (Journal of the College of Education for Women, 2019)
This paper aims at exploring the impact of the Iraq-Iran war in the poetry of Adnan Al-Sayegh. Al-Sayegh participation in this war makes him a first hand witness to the atrocities of the trenches and fight in the first lines. This war did not only change his life and world view for good, it changes the nature of his poetry as well. As aresult, war becomes a central issue not only in the poetry Al-Sayegh wrote in the 1980s and 1990s Iraq, but also in the exile.Key Words: War, Al-Sayegh, Poetry.